U-Pb geochronology and structural geology across major shear zones of the Southern granulite terrain of India and organic carbon isotope stratigraphy of the Gondwana coal basins of India : their implications for Gondwana studies - Ghosh, Joy Gopal (Department of Geological Sciences, 2014)
Bibliography: p. 277-308.